1967
DOI: 10.1002/jcp.1040690315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of helium group gases and nitrous oxide on hela cells

Abstract: The helium group gases and nitrous oxide at superatmospheric pres- In a systematic study of the effects of the helium group gases on linear growth of Neurospma crassa, Schreiner, Gregoire and Lawrie ('62) showed that helium group gases depressed the rate of growth as a function of the square root of the molecular weight. These observations were extended by Buchheit, Schreiner and Doebbler ('66) by employing these gases at higher pressures. They obtained a linear correlation between the 50% inhibitory pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1969
1969
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Taylor (20) found that even highly compressed He at 50 MPa was able to reduce the inhibitory effect of 50 MPa of hydrostatic pressure for growth of a marine pseudomonad. The studies of Bruemmer et al (2) with HeLa cells in monolayer culture indicated little inhibitory effect of He, Ne, or N2 except at pressures above ca 5 MPa. Ar caused a 25% reduction in cell count at a pressure ca.…”
Section: Discussionmentioning
confidence: 92%
“…Taylor (20) found that even highly compressed He at 50 MPa was able to reduce the inhibitory effect of 50 MPa of hydrostatic pressure for growth of a marine pseudomonad. The studies of Bruemmer et al (2) with HeLa cells in monolayer culture indicated little inhibitory effect of He, Ne, or N2 except at pressures above ca 5 MPa. Ar caused a 25% reduction in cell count at a pressure ca.…”
Section: Discussionmentioning
confidence: 92%
“…The inactive gas (He) that was used for preservation has anesthetic action (8) and metabolic suppression action (3), and inactive gases such as Xe are used for preserving plants (31).…”
Section: Discussionmentioning
confidence: 99%
“…Theories regarding the mechanisms of these effects of CO 2 include theories that it is adsorbed on the surface of a protein biopolymer (14) or theories that the main cause of the effects is that it structures collections of water molecules in living organisms (24), just like inert gases such as Xe that are, just like CO 2 , used for their anesthetic mechanism (7), their decomposition-inhibiting mechanism (3), or for the preservation of plants (28). In addition, it is believed that decreases in pH that occur with the dissolution of CO 2 are also involved, although this has yet to be fully understood.…”
Section: Discussionmentioning
confidence: 99%